KARYA SASTRA: MIMESIS, REALITAS ATAU MITOS? - Muzakki, Akhmad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2007)
Literature is represents falsehood, said Rahdar, but it is used as a unique procedure to reveal the truth. The imagination worldÂ  ia as a contact or touch between idea and language that create literary works in certain case and it becomes the autonomous area which are not necessary to be related to the reality. Although it is imaginative, it must not be irrational because the imaginative thing is also possible to happen in real life. As a work of imagination, literary work is not able to place itself as a central of legal social problems. It is caused by the fact that literary work is an imaginative work which contraries to reality so the harmony between mimesis and author's creativity to create the new thing has great role in creating the quallified literature.